Fiscal Dominance in Sub-Saharan Africa Revisited. (IMF Working Papers; Working Paper, 2021)
This paper explores the causes and consequences of fiscal dominance over monetary policy in Sub-Saharan Africa (SSA). Fiscal dominance has always been a pressing problem as it can contribute to inflation and macroeconomic instability, and increasingly so as fiscal deficits and public debt are rising in many SSA countries. We find that legal limits and availability of alternative financing options play an important role in determining the extent to which government deficits tend to be financed by the central bank. We also find economically significant effects of central bank lending to government on the exchange rate and inflation.